ANALISIS RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PT ACE HARDWARE INDONESIA PERIODE 2021-2024 - Ni Made Arsita Kusumadewi; Miftahul Hariz; Erwin Putra Rasul Dafana; Ivonia Auxiliadora Freitas Marcal; Yosse Putra Oentoro; I Made Suparta (widya balina, 2025)
Abstract. This study aims to analyze the effect of Return On Equity (ROE) on stock prices at PT Ace Hardware Indonesia Tbk during the 2021–2024 period. The background of this research emphasizes the importance of the capital market as a means of investment and a source of corporate funding, as well as the need for financial ratio analysis in investment decision-making. This research employs a quantitative approach using descriptive statistical analysis and multiple regression methods. The data analyzed includes the company's annual ROE and stock price values. The results indicate fluctuations in both ROE and stock prices over the period. Although ROE declined in 2022, it showed a subsequent upward trend. The drop in ROE during 2022 coincided with a sharp decline in stock prices, presumably due to unmet investor expectations. The main finding reveals a positive relationship between ROE and stock prices, where an increase in ROE tends to be followed by a rise in stock prices. This suggests that ROE is a crucial indicator for investors in evaluating company performance and investment prospects. The study concludes that improving capital utilization efficiency through a high ROE can enhance the attractiveness of a company's stock in the capital market.